A High voltage-gain boost converter with coupled-inductor. (2nd January 2018) - Hsieh, Yao-Ching; Alam, Mohammd Mahmood; Lin, Zhong-Rong; Lin, You-Cheng; Lin, Jing-Yuan; Chiu, Huang-Jen
Abstract: This paper presents a novel high voltage-gain boost converter with coupled-inductors. The proposed converter consists of two pairs of coupled-inductors to collect energy in parallel and release energy to the load in series, which provides a much higher step-up ratio than conventional boost converter. The non-unity turns ratio helps reduce the voltage stress on the active switches and leads to lower conduction losses. The control is simple and similar to that of a conventional boost converter. A 200 W prototype circuit is designed and implemented to verify the correctness and feasibility of the circuit. The step-up ratio in the experiment is higher than 26, and the highest efficiency is 93.9%.